MAINTENANCE OF FORM, MEANING AND FUNCTION MINANGKABAU ORAL LITERATURE IN DENDANG DAREK ON INDUSTRIAL ERA 4.0 (PEMERTAHANAN BENTUK, MAKNA DAN FUNGSI SASTRA LISAN MINANGKABAU DALAM DENDANG DAREK DI ERA INDUSTRI 4.0) - Amran Amran; Maryelliwati Maryelliwati; Syafniati Syafniati; M. Arif Anas (Universitas PGRI Sumatera Barat, 2020)
Minangkabau oral literature has a kind of Nagari arrogance, meaning that a genre that is in an area is not usually developed in other regions, but other regions can appreciate the genre well, even inviting it to be displayed in its area (which is not its origin), for example dendang darek. The problem in this research is the many different forms of the dendang darek, whether it still survives in the times, so this research will look at how to maintain the form, function and meaning of Minangkabau oral literature dendang darek in the industrial era 4.0. Based on that, the research objective is to describe the retention of the form, function, and meaning of Minangkabau oral literature in the industrial era 4.0. This research uses a qualitative approach with descriptive methods. The results showed that the form of Minangkabau oral literature dendang darek is inseparable from the noble values of the Minangkabau culture, which has been passed down from one generation to the next. Dendang darek functions as a means of expressing emotional expression, aesthetic dialogue, a means of conflict management training, self and group existence, social control, and a means of collecting social funds. The meaning contained in dendang darek is an embodiment of moral and ethical messages so that someone acts according to the teachings of adat and religion.